Assessment of the Development of the Circular Economy in the EU Countries: Comparative Analysis by Multiple Criteria Methods - Dainora Gedvilaitė; Giedrė Lapinskienė; Marek Szarucki (Emerging Science Journal, 2024)
In recent decades, attention to environmental resource management has increased worldwide. Circular economy (CE) is a concept that is increasingly being considered as a solution to this range of challenges. Therefore, it is important to monitor the development of CE. This research is an attempt to contribute to the CE surveillance literature by providing a framework for comparing the positions of states and their classifications. The main goal of the article is to assess the level of circular economy development in EU countries according to the chosen methodology. The indicators used in this study are sourced from the European Commission Monitoring Framework database, which includes data from 27 European Union (EU) countries over the time frame from 2016 to 2020. The analysis was carried out using Multi-Criteria Decision Methods (MCDM), such as Simple Additive Weighing (SAW), and the objective method of estimating weights in accordance with proportional differences (APROD), which helped to assess the state of CE. The results showed that EU countries can be divided into three groups based on the level of performance of the CE, and their level of development in relation to the circular economy is different. The level of circular economy development in most EU countries is low. Germany, the Netherlands, France, and Italy demonstrated the best positions. The study findings were derived from the combination of two MCDMs, thus increasing the refinement of the overall methodology. Doi: 10.28991/ESJ-2024-08-02-013 Full Text: PDF